Monsters in the Cupboard - Dougherty, John; Illustrated by Dave Williams (UK Rising Star, 2016)
When Sam and Bansi go to collect supplies from the school art cupboard, the shelves are bare! Something, or someone, has eaten all the paper, glitter and glue! Could it be monsters?! Find out in this amusing playscript, designed for reading or performing.
Including color illustration
Keywords: Monsters -- Readers (Elementary)